2012
DOI: 10.1152/ajpcell.00284.2011
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor deficiency worsens inflammation and lymphedema after lymphatic injury

Abstract: Mechanisms regulating lymphedema pathogenesis remain unknown. Recently, we have shown that lymphatic fluid stasis increases endogenous danger signal expression, and these molecules influence lymphatic repair (Zampbell JC, et al. Am J Physiol Cell Physiol 300: C1107-C1121, 2011). Endogenous danger signals activate Toll-like receptors (TLR) 2, 4, and 9 and induce homeostatic or harmful responses, depending on physiological context. The purpose of this study was to determine the role of TLRs in regulating tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 56 publications
7
51
0
Order By: Relevance
“…These findings are consistent with previous studies demonstrating that macrophages play active roles in the regulation of fibrosis in other organ systems (6,33). In addition to other studies, consistent with known roles of macrophages in the regulation of lymphangiogenesis (7,8,23), we have shown that macrophages in lymphedematous tissues strongly express VEGF-C (33)(34)(35)(36). However, although it is clear that lymphedema promotes macrophage infiltration, the precise role of these cells in the regulation of fibrosis and lymphangiogenesis in response to sustained lymphatic fluid stasis has not been assessed through direct loss-of-function studies.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previous studies demonstrating that macrophages play active roles in the regulation of fibrosis in other organ systems (6,33). In addition to other studies, consistent with known roles of macrophages in the regulation of lymphangiogenesis (7,8,23), we have shown that macrophages in lymphedematous tissues strongly express VEGF-C (33)(34)(35)(36). However, although it is clear that lymphedema promotes macrophage infiltration, the precise role of these cells in the regulation of fibrosis and lymphangiogenesis in response to sustained lymphatic fluid stasis has not been assessed through direct loss-of-function studies.…”
supporting
confidence: 93%
“…However, we have also previously reported that the number of macrophages in the lymphedematous tissues is increased substantially compared with controls (37). In addition, in a recent report using a mouse tail model of lymphedema, we found that animals lacking Toll-like receptors had decreased macrophage accumulation and increased fibrosis/adipose deposition (35). These findings are consistent with previous studies demonstrating that macrophages play active roles in the regulation of fibrosis in other organ systems (6,33).…”
supporting
confidence: 92%
“…Inflammation has been shown to play an important role in determining the amount of swelling in lymphedema (22,45,46) and may be an important stimulus promoting the appearance and perpetuation of the swelling (8). Indeed, the initial appearance of the chronic form of lymphedema in the human can occur rapidly (within a few hours to days) following an acute inflammatory insult (4), although subsequently it may slowly worsen.…”
mentioning
confidence: 99%
“…54 Studies in a mouse model of post-surgical lymphedema deficient for TLR2, TLR4, and TLR9 demonstrated significantly worse effects post injury compared with those in a wild-type model, as evidenced by increased tissue edema, reduced lymphangiogenesis, increased fibrosis, and increased leucocyte infiltration but reduced monocyte infiltration. 55 The data suggest a role for TLRs in the normal repair of lymphatic injury and resolution of lymphedema. 55 Consequently, although TLRs appear to have a role in normal inflammation and swelling, their role in the diabetic patient with lymphedema may be confused, and the excessive TLR-mediated inflammation associated with diabetes is counterproductive with resultant chronic lymphedema.…”
Section: Cellular Component In Dfu and Lymphedemamentioning
confidence: 94%
“…55 The data suggest a role for TLRs in the normal repair of lymphatic injury and resolution of lymphedema. 55 Consequently, although TLRs appear to have a role in normal inflammation and swelling, their role in the diabetic patient with lymphedema may be confused, and the excessive TLR-mediated inflammation associated with diabetes is counterproductive with resultant chronic lymphedema.…”
Section: Cellular Component In Dfu and Lymphedemamentioning
confidence: 94%